2016
DOI: 10.4186/ej.2016.20.4.129
|View full text |Cite
|
Sign up to set email alerts
|

A New Trend of Physical Concentration in Resources Recycling

Abstract: Abstract. Physical separation is one of the key technologies in the field of resources recycling for concentrating targeted component(s) and could create an environment friendly recycling process because of their relatively low energy consumption and low cost required. Physical separation process involves two kinds of stages, one is comminution for achieving the liberation of targeted component(s) and the other is real separation of target component(s) from the others. Recently a variety of smart comminution p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…43) Furthermore, based on mathematical calculation and modeling, Owada's group reported that heating-quenching of spent catalysts will be a useful pretreatment step for the physical concentration of PGMs. 42,44) When spent catalysts are heated to 600800 °C and subsequently quenched in water, the interface between the catalyst layer and substrate cracks due to differences in their thermal expansion rates. After thermal shock and appropriate pulverization, PGMs are expected to be more efficiently concentrated by particle size sorting.…”
Section: Physical Concentration Of Pgms In Spent Catalystsmentioning
confidence: 99%
“…43) Furthermore, based on mathematical calculation and modeling, Owada's group reported that heating-quenching of spent catalysts will be a useful pretreatment step for the physical concentration of PGMs. 42,44) When spent catalysts are heated to 600800 °C and subsequently quenched in water, the interface between the catalyst layer and substrate cracks due to differences in their thermal expansion rates. After thermal shock and appropriate pulverization, PGMs are expected to be more efficiently concentrated by particle size sorting.…”
Section: Physical Concentration Of Pgms In Spent Catalystsmentioning
confidence: 99%